Elegant and Practical: Bindings of Books Printed in the Middle of 16th and the First Half of the 17th Centuries in Italy and the Polish–Lithuanian Commonwealth in the Library of Vilnius Jesuit Academy - Rusteikaitė, Ieva (Knygotyra, 2023)
In the early modern period, the relentless growth in the copies of printed books and the increasing competition between craftsmen meant that, since the invention of Gutenberg until the 19th century, European bookbinders were forced to look for cheaper and quicker binding techniques. Based on this assumption, the article focuses on some of the bindings of books printed from the middle of the 16th until the middle of the 17th century which belonged to the library of Vilnius Jesuit Academy. This study is part of a broader research on the bindings of the Vilnius Jesuit Academy Library, and the article is limited to two groups of sources: books printed in Italy and books printed in the Kingdom of Poland and the Grand Duchy of Lithuania (Polish–Lithuanian Commonwealth). The historical bindings are discussed by following the approach targeting the field of decorative arts and material culture studies, which is also well known as the ‘archaeology’ of the book or the bookbinding. It focuses not only on the decorative features of the cover of the book, but also on the structural features of the bindings which reveal comprehensively the work of the craftsmen of the past. This method of analysis is particularly useful for discussing not only decorated but also undecorated bindings which have so far received very limited attention in the research of the old Lithuanian book. As a result, the research revealed that the modest parchment bindings form nearly a half of all the examined bindings of the collection, and confirm the practical rather than the representational aspect of the Jesuit Library. According to the complexity of the technical execution and the number of operations involved in the process of binding, five binding techniques have been distinguished, ranging from the most complex to the simplest bindings, closely related with a retail bindings. What is more, a consistent number of parchment bindings are denoted by structural features, which is close to the Italian bookbinding tradition. The predominance of the latter in the group of Italian prints makes it possible to consider the possibility of already bound books entering the library of Vilnius Jesuit Academy. Moreover, the research has revealed certain binding features linked to the bookbinding traditions in Italy and the Polish–Lithuanian Commonwealth.
Keywords: printing; bookbinding; Library of Vilnius Jesuit Academy; retail bindings; Italian bindings